Peer Relationships, Academic Motivation, Academic Self-Efficacy, and Student Achievement: Moderated Mediation Model - Nilam Septi Ariria Rachmawati; Eka Indah Nurlaili; Retno Mustika Dewi (Economics Education Department Universitas Negeri Semarang, 2024)
This study utilizes statistical approaches and hypothesis testing to explore the relationships among variables in the context of peer relationships, academic motivation, academic self-efficacy, and economic learning outcomes among 10th-grade students at Surabaya Public Senior High School 12. It employs a quantitative research design with a sample of 191 10th-grade students from Surabaya Public Senior High School 12. Data collection is conducted through a Likert-scale questionnaire, which is then analyzed using descriptive statistics, correlation analysis, and moderated mediation analysis using the PROCESS Hayes Model 7 method. The results of the study indicate significant relationships among the variables under investigation. Peer relationships (PR) have a positive impact on academic motivation (AM), academic self-efficacy (ASE), and economic learning outcomes (EO). Similarly, the relationship between academic motivation and economic learning outcomes also shows a positive impact. Furthermore, it is found that academic motivation mediates the relationship between peer relationships and economic learning outcomes. Academic self-efficacy also moderates the relationship between peer relationships and academic motivation, where this moderating effect reduces the strength of the expected mediation effect.